Implementation of an Accounting Information Systems for Fast Secure Credit - Yuliana; Haliah; Nirwana (Jurnal Multidisiplin Madani, 2023)
This study aims to analyze the use of an accounting information system for providing fast secure credit at PT Pegadaian Pelita Makassar branch. Fast Safe Credit is a credit that aims to provide loans for customers based on pawn law with fast procedures, easy regulations, and safe with loans ranging from fifty thousand rupiah to one billion rupiah. The research uses a qualitative approach with primary data from interviews with appraisers, collateral managers, and cashiers. Secondary data from documents on secured fast lending. The results showed that PT Pegadaian has used an accounting information system and has succeeded in supporting the smooth provision of fast and secure credit, especially through the PASSION application to facilitate the process of applying for and granting credit